login
E.g.f. satisfies A(x)^(A(x)^2) = 1/(1 - x*A(x)).
2

%I #11 Jul 16 2022 11:50:15

%S 1,1,0,6,-4,300,-828,42224,-266992,11916864,-132472320,5688511488,

%T -95465876064,4138883728512,-95019458907072,4276023328128000,

%U -125481256750340352,5958015717717504000,-212934915549001078272,10767675634298110255104

%N E.g.f. satisfies A(x)^(A(x)^2) = 1/(1 - x*A(x)).

%F a(n) = Sum_{k=0..n} (n-2*k+1)^(k-1) * |Stirling1(n,k)|.

%o (PARI) a(n) = sum(k=0, n, (n-2*k+1)^(k-1)*abs(stirling(n, k, 1)));

%Y Cf. A001761, A141209.

%Y Cf. A355768.

%K sign

%O 0,4

%A _Seiichi Manyama_, Jul 16 2022